Intersecção dos dispositivos midiáticos e religiosos: a midiatização como lógica do consumo na igreja Universal do Reino de Deus - Bandeira, Alexandre Dresch (Universidade do Vale do Rio do Sinos, 2006)
This dissertation only expressed the investigation on the Universal Church Kingdom of God (IURD) in the perspective of the processes midiáticos. Theoretically, he/she contemplates starting from the concepts of electronic church, devices and fields midiáticos. Empirically, he/she grows starting from observation procedures and documental research. the method of construction of analyses followed a descriptive lineage, of successive formulation, using several analytical resources, besides visual outlines (maps, plants, organization charts, images and pictures), until approaching of central concepts around which we tried to think the midiático in this Church. This analysis tries to show the whole process midiático through the intercession of the devices midiáticos and religious persons, involving the several concepts in the studied problems, with the intention of trying to understand like IURD works in the field midiático, mixing practices of the consumption logics with the one of religion
Keywords: campo das mídias; dispositivos midiáticos; tele-evangelismo; devices; field of mídias; tele-evangelism; midiatização; Ciências Sociais Aplicadas